Investigation of the effect of humidity at both electrode on the performance of PEMFC using orthogonal test method. (21st May 2019) - Wang, Bohan; Lin, Rui; Liu, Dengcheng; Xu, Ji; Feng, Bowen
Abstract: Under the vehicle working conditions, operating temperature and relative humidity (RH) of gas supplies have an important influence on the performance and durability of PEMFC. In this paper, the influence of hydrogen RH, air RH, operating temperature and air stoichiometric ratio on the performance of PEMFC was studied with the help of 5 factors and 4 levels orthogonal test table. The fifth factor was set to be empty to carry out the variance analysis. Using variance analysis method, the influence degree of random errors on the experiments was analyzed. The credibility of the experimental results was verified along with the polarization curve and the electrochemical impedances spectroscopy (EIS) results. The experiment results show that the most important factor which affects the performance of PEMFC is air stoichiometric ratio, followed by air RH, and then the operating temperature. The effect of hydrogen RH on PEMFC performance is minimal and negligible. Low hydrogen RH can be used during operation to reduce energy consumption of auxiliary system. Highlights: The influence of humidity at both electrode on the performance of PEMFC was investigated based on orthogonal test method. Air relative humidity (RH) has also a great impact on PEMFC while the hydrogen RH has almost no influence on its performance. The influence of hydrogen RH is even smaller than test error.